Grand canonical Monte Carlo simulations of pore structure influence on methane adsorption in micro-porous carbons with applications to coal and shale systems. (1st March 2018) - Song, Wenhui; Yao, Jun; Ma, Jingsheng; Li, Aifen; Li, Yang; Sun, Hai; Zhang, Lei
Highlights: The influence of pore structure on methane adsorption was investigated. Grand canonical Monte Carlo was applied to estimate the adsorption isotherms. Four types of pores with different structures were constructed. It is important to characterize pore structure when estimating adsorption capacity. Abstract: Coal and shale are strong heterogeneous anisotropic media involving nanoscale pore size and variance of microstructure. The complexity of methane adsorption is expressed both in diverse chemical properties and confined pore structures. In this study, Grand canonical Monte Carlo simulations were carried out to assess the influence of pore structure on methane adsorption at temperature 318 K, 333 K and pressure up to 20 MPa. The pore radii of physical carbon-based model range from 0.55 nm to 1.15 nm at the step of 0.1 nm. Simulated results indicate that the excess adsorption isotherms and maximum excess adsorption density are notably different for different pore structures. The triangle pore exhibits largest value of maximum excess adsorption density followed by the slit pore, circle pore and square pore. The maximum excess adsorption density is larger than 6 × 10 3  mol/m 3 at simulated temperatures for triangle pore with pore radius less than 1 nm. The excess adsorption amount first increases with the increase of pressure and then decreases when the pressure is larger than 7.5 MPa for slit pore and 5 MPa for the circle pore, triangle pore and square pore. The excess adsorption amount for circle pore and square pore drops down to negative value when the pressure is larger than 12.5 MPa while the excess adsorption amount stays above zero across simulated pressure for the slit pore and triangle pore. The adsorption isotherms of micro-porous carbons were obtained by superposition of simulated adsorption isotherms based on the pore size distribution and were compared with coal samples experimental data gathered from the same temperature. The experimental isotherm is more close to slit pore excess isotherm and predicted excess isotherms based on circle pore and square pore under-estimate excess adsorption capacity.